Analysis of Needs and Weaknesses of The Maternal and Child Health Surveillance System - Hasanuddin, Asni (International Journal of Public Health Excellence (IJPHE), 2024)
The maternal and child health program in Sukoharjo district includes several reports on childbirth, postpartum, immunization reports, nutritional counseling, midwife courses, home visit reports, and family planning services, both in hospitals, health centers, maternity homes, and midwives. The maternal and child health surveillance that has been carried out so far has only been carried out to fill in data reports to health agencies at the central level. It has not been presented and analyzed properly, let alone disseminated the information to those who need it. Therefore, efforts are needed to improve the quality of epidemiological data and information so that planning and evaluation are well coordinated to improve the quality of the analysis results of surveillance data studies in terms of timeliness and sensitivity of reports. This research aims to determine the weaknesses in the need for a maternal-child health surveillance system and a maternal-child health surveillance system. The intervention method used is through on-the-job training. Meanwhile, district officers who have been trained previously (tiered training) train maternal and child health workers at community health centers. From the results of the analysis, it can be concluded that the maternal and child health program surveillance system is generally running well.